Ser80Ile mutation and a concurrent Pro25Leu variant of the VHL gene in an extended Hungarian von Hippel-Lindau family - Fazakas Ferenc; Toth Miklos; Balogh Katalin; Gergics Peter; Patocs Attila; Liko Istvan; Racz Karoly (BMC, 2008)
Abstract Von Hippel-Lindau disease (VHL) is a rare autosomal dominant disease characterized by development of cystic and tumorous lesions at multiple sites, including the brain, spinal cord, kidneys, adrenals, pancreas, epididymis and eyes. The clinical phenotype results from molecular abnormalities of the VHL tumor suppressor gene, mapped to human chromosome 3p25-26. The VHL gene encodes two functionally active VHL proteins due to the presence of two translational initiation sites separated by 53 codons. The majority of disease-causing mutations have been detected downstream of the second translational initiation site, but there are conflicting data as to whether few mutations located in the first 53 codons, such as the Pro25Leu could have a pathogenic role. In this paper we report a large Hungarian VHL type 2 family consisting of 32 members in whom a disease-causing AGT80AAT (Ser80Ile) c.239G>A, p.Ser80Ile mutation, but not the concurrent CCT25CTT (Pro25Leu) c.74C>T, p.Pro25Leu variant co-segregated with the disease. To our knowledge, the Ser80Ile mutation has not been previously described in VHL type 2 patients with high risk of pheochromocytoma and renal cell cancer. Therefore, this finding represents a novel genotype-phenotype association and VHL kindreds with Ser80Ile mutation will require careful surveillance for pheochromocytoma. We concluded that the Pro25Leu variant is a rare, neutral variant, but the presence such a rare gene variant may make genetic counseling difficult.